The Effectiveness of Consumer Protection Arrangements in E-Commerce Transactions on the Shopee Marketplace Platform in Indonesia - Irfan, Mochamad; Negara , Dharma Setiawan (Journal of Social Science Studies, 2023)
Consumer protection in e-commerce transactions in Indonesia, especially on marketplace platforms such as Shopee, has become an important issue along with the rapid development of technology and the increase in digital transactions. The regulations, which include Law No. 8/1999 on Consumer Protection, Government Regulation No. 80/2019 on Trading through Electronic Systems, and Law No. 19/2016 on Electronic Information and Transactions (ITE), provide a clear legal basis for consumer protection. However, the implementation of these regulations requires more effective supervision, strict enforcement of sanctions, and a clear dispute resolution mechanism. In addition, the role of marketplace platforms in ensuring transaction security and protection of consumers’ personal data is also crucial. Stricter supervision from the government and increased transparency from platforms will provide more assurance for consumers in transacting online. This research aims to explore the effectiveness of consumer protection regulations on the Shopee marketplace platform, as well as the challenges and solutions that can be taken to improve such protection.